Agroclimatic zone classification for rice and sugarcane using NOAA (AVHRR) data for the Northeast, Thailand - Somchai Baimoung; Apisit Eiumnoh; Tawatchai Tingsanchali; Kaew Nualchawee; Royal Thai Government (RTG) (Bangkok : Asian Institute of Technology, 1994)
The study undertaken was aimed at defining the appropriate agroclimatic zones for rice and sugarcane cultivated areas of the Northeast of Thailand using the integration of remote sensing and GIS techniques. Specifically it illustrated the onset time, end time and numbers of days of growing period for such crops which the results will be useful to the planner and policy makers in formulating the policy guidelines to agricultural development program and also to the agri"cultural officials or farmers for seasonal timing and selecting the crops appropriate to a specific locality and climate with the result that it has provided a great deal of improvement to future agricultural production.
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: Crops and soils -- Thailand, Northeastern; Crops and climate -- Thailand, Northeastern; Remote sensing